SME, Digital Marketing Analysis On The Usage Advantages Of Marketplace For MSMES In Lampung - Murdiani, Trufi (International Journal of Economics, Business, and Entrepreneurship, 2021)
The product sales for MSMEs need a technology support. One of this certain technology is a digital media which has been rapidly develop many business actors. Since the pandemic occured, the problem on how to use the digital media such as marketplace faced some MSMEs actors. Marketplace as the most effective tool in order to increase marketing activities still does not give a chance for some MSMEs actors to improve their business. This research was done by qualitative method to prove the effectiveness of digital marketing media especially marketplace for small business people who were directly involved with online marketing. The research method was done by interviewed approaches and analysis on the problem as well as find the solution on how to achieve the success in using digital media namely marketplace. Through this research, it was expected that small businesses could choose wisely and effectively the digital media namely marketplace on their marketing activities to increase product’s sell.